2021
DOI: 10.7717/peerj.12015
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between characteristics of root morphology and grain filling in wheat under drought stress

Abstract: Drought is a common yield limiting factor in wheat production and has become a significant threat to global food security. Root system is the organ responsible for water uptake from soil and root growth is closely associated with yield and quality of wheat. However, the relationship between morphological and structural characteristics of root growth and caryopsis enrichment in wheat under drought stress is unclear. In this study, two wheat cultivars (YM13 and YN19) were treated with drought from flowering to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
7
18
0
Order By: Relevance
“…In this study, we used our model to look at the effect of a dry and warm spell of one week on plant water flow, carbon flow, and growth, based on the expected temperature, air relative humidity, and relative variation in soil water content in Germany for June of 2100 (but without changes of CO 2 concentrations). We could observe a lower growth rate for all organ, fitting with the results of Chen et al [10] for monocots under drought stress. In this simulation, the lower growth was caused by a too low 32 turgor pressure rather than a lack of sucrose.…”
Section: Results Of the Simulationsupporting
confidence: 90%
“…In this study, we used our model to look at the effect of a dry and warm spell of one week on plant water flow, carbon flow, and growth, based on the expected temperature, air relative humidity, and relative variation in soil water content in Germany for June of 2100 (but without changes of CO 2 concentrations). We could observe a lower growth rate for all organ, fitting with the results of Chen et al [10] for monocots under drought stress. In this simulation, the lower growth was caused by a too low 32 turgor pressure rather than a lack of sucrose.…”
Section: Results Of the Simulationsupporting
confidence: 90%
“…This may be attributed to physiological and biochemical disturbances that affect the regulation of stomatal opening and chlorophyll biosynthesis, which are essential for photosynthesis (Aurangzaib et al, 2021). These results corroborate those of Chen et al (2021), who found that wheat plants had a lower height when there was soil water restriction. On the other hand, the plant height of the other studied genotypes, BRS 264 and BRS 394, was stimulated by soil water deficit (45 kPa).…”
Section: Resultssupporting
confidence: 83%
“…The filling stage is the most rapid stage of wheat grain development, and photosynthetic capacity during this period strongly affects yield. Meanwhile, drought stress at the wheat filling stage has a significant impact on photosynthesis and wheat yield [ 65 , 66 ]. Therefore, it is important to estimate the chlorophyll content of wheat under drought stress in the filling stage for screening the drought-resistant wheat varieties.…”
Section: Methodsmentioning
confidence: 99%